Estilo de liderazgo pasivo-evitador e intercambio de comportamientos líder-seguidor en estudiantes universitarios: una aproximación desde Chile (2020)
This article analyzes the effect that passive-avoidant leadership style has on the exchange of leader-follower behaviors in college students, in addition to the effect of the nature of the team on this relationship. To this end, a study was conducted on 181 individuals from 32 student teams at a Chilean university, and a multilevel structural equation modeling was used for data analysis. Findings indicate that the passive-avoidant leadership style is negatively related to the exchange of leader-follower behaviors, and that students who are more advanced in the curriculum positively encourage the adoption of both behaviors. In addition, when team members have not made much progress in the curriculum, the relationship between passive-avoidant leadership style and the exchange of leader-follower behaviors changes and becomes positive. Finally, the impact of these findings on teams of higher education students and the importance of understanding leadership in a team context are discussed.